Technology-Performance Nexus during Covid-19: A Case of Commercial Banks from Selected South Asian Economies - Syed Muhammad Abdul Rehman Shah; Kashif Raza; Asif Raza; Ismat Nasim (iRASD Journal of Management)
Technology acceptance affects performance of employees in emerging organizations. This study explores the relationship between technological transformation and performance of the employees of commercial banks from selected Asian economies during Covid-19 pandemic. We also analyze the effect of moderators; training, supervisor support and incentives on this relationship. We have tested the hypotheses by means of the survey of 400 employees of commercial banks from selected South Asian economies of Bangladesh, India, Sri Lanka, Maldives, and Pakistan. The Pearson correlation and multiple linear regression techniques are utilized to investigate the research problem. The identity theory and social learning theory reflects that the individuals get satisfied while relating themselves with the objectives of organization and the goals of nation. Further, they participate in the organizational and national development through technical innovation process if provided with supervisory support, training and incentives. This study recommends to executive management to adopt modern technology for sake of the higher objectives of firms’ performance in a Post- Covid depressed economies.